2023
DOI: 10.3389/fmicb.2023.1106888
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the soil fungal community structure of Larix gmelinii forests in Northeast China

Abstract: Soil fungi play an indispensable role in forest ecosystems by participating in energy flow, material circulation, and assisting plant growth and development. Larix gmelinii is the dominant tree species in the greater Khingan Mountains, which is the only cold temperate coniferous forest in China. Understanding the variations in underground fungi will help us master the situation of L. gmelinii above ground. We collected soil samples from three seasons and analyzed the differences in soil fungal community struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…During the drier season, soil fungal abundance decreases compared to the wet season, but fungal diversity increases (Kivlin and Hawkes, 2016). In our previous study, variations in temperature and precipitation were important factors influencing seasonal changes in the fungal communities (Zhao et al, 2023). In fact, seasonal changes were masked by sites in this study.…”
Section: The Effect Of Seasonal Changes On Soil Fungal Communitiesmentioning
confidence: 50%
See 1 more Smart Citation
“…During the drier season, soil fungal abundance decreases compared to the wet season, but fungal diversity increases (Kivlin and Hawkes, 2016). In our previous study, variations in temperature and precipitation were important factors influencing seasonal changes in the fungal communities (Zhao et al, 2023). In fact, seasonal changes were masked by sites in this study.…”
Section: The Effect Of Seasonal Changes On Soil Fungal Communitiesmentioning
confidence: 50%
“…Seasonal changes in temperature and precipitation are also responsible for variations in soil fungal communities (Tedersoo et al, 2014;Zhang et al, 2018). In our previous study, temperature and precipitation were found to be the most important factors affecting fungal diversity with seasonal variations (Zhao et al, 2023). As for spatial differences, soil fungal communities have different structures between geographic sites, and their physicochemical properties directly constitute different fungal living environments, such as nitrogen (Zhou et al, 2016), pH (Zhang et al, 2016), and moisture (Zumsteg et al, 2013).…”
Section: Introductionmentioning
confidence: 90%
“…A study in Austria found no Populus tremula- associated EcM taxa that were significantly associated with summer or autumn conditions ( Krpata et al, 2008 ). Yet many studies have found significance of seasonal factors on fungal relative abundance ( Zhao et al, 2023 ) and community compositions ( Vargas-Gastélum et al, 2015 ; Beidler et al, 2023 ). Others have suggested that host-tree characteristics have more impact than the seasonal factor alone in describing changes in fungal communities ( Park et al, 2020 ), thus the seasonal factor should be considered in interaction with tree or site characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends also emerged for Acaulospora and Paraglomus (Figure 9B). This finding was associated with an increase in apoplastic substances during the winter season, as well as diminished growth rates of plants resulting from lower temperature and precipitation relative to the summer season [19].…”
Section: Correlation Analysis Of Soil Chemical Properties and Amf Com...mentioning
confidence: 98%